PURIFICATION AND PROPERTIES OF AN EXTRACELLULAR PROTEASE PRODUCED BY PENICIUIUM EXPANSUM (Journal of Sciences, Islamic Republic of Iran)
Penicilliurn expamum grown in a medium with rice husk as a carbon source produced an extracellular protease. The protease enzyme was isolated from culture broth by fractionation with acetone and column chromatography on Sephadex G- 100 and DEAE A-50. The protease enzyme was purified about 17.47 fold, with a recovery of 14%. The purified protease was homogenous on SDS polyacrylarnide disc gel electrophoresis and molecular weight was calculated to be 28000. The optimum activity of protease was found at pH 7.5 and temperature 30°C. The enzyme activity was enhanced on addition of Ca , Zn , Co and Mn whereas inhibition was observed in the presence of EDTA, Hg and Ag . Addition of cysteine and 2- mercaptoethanol did not produce any significant effect on protease activity